The Difficult Art of Giving : Patronage, Philanthropy, and the American Literary Market - Sawaya, Francesca (Book collections on Project MUSE., 2014)
The Difficult Art of Giving rethinks the economic history of American literature, demonstrating that the practices of patronage and corporate-based philanthropy shaped the literary market . Francesca Sawaya examines the importance of patronage and philanthropy on major post-bellum authors' careers and fiction.